Germline mutations in DNA repair genes are associated with bladder cancer risk and unfavourable prognosis. (4th June 2018) - Na, Rong; Wu, Yishuo; Jiang, Guangliang; Yu, Hongjie; Lin, Xiaoling; Wang, Meilin; Conran, Carly A.; Fantus, Richard J.; Zhang, Ning; Liu, Shenghua; Helfand, Brian T.; Zheng, Siqun L.; et al.
Abstract : Objectives: To perform a systematic evaluation of whether germline DNA repair gene mutations in bladder cancer (BCa) are associated with increased risk of BCa and aggressive disease. Materials and Methods: Germline DNA from 98 patients with BCa was analysed for 54 DNA repair genes using a customized targeted sequencing panel. Population control data were obtained from the public databases the Exome Aggregation Consortium database and the Genome Aggregation Database. Mutation pathogenicity was annotated based on American College of Medical Genetics criteria, mutation frequencies in the general population and the ClinVar database. Mutation frequencies were compared based on case–control and case–case designs for disease risks, disease aggressiveness and outcomes. Results: The frequency of pathogenic/likely pathogenic germline DNA repair gene mutations was 10.2% among patients with BCa. Within the subset of patients with carcinoma invading the bladder muscle, the frequency was 15.8%, ~2.4‐fold higher than in patients with non‐muscle invasive BCa (6.67%). The mutation frequency among patients with early‐onset disease (at age <45 years) was ~3‐fold higher than among those diagnosed after age 45 years (28.57% vs 8.79%). Mutation carriers had a significantly higher frequency of unfavourable clinical outcomes (disease recurrence or progression to metastatic BCa) than non‐carriers (50.0% vs 13.64%; P = 0.013). Conclusion: Pathogenic and likely pathogenic mutations in DNA repair genes were associated with unfavourable prognosis of BCa.